Effective utilization of processors in computer cluster when solving problems of various parallelizable scales - Petkus, Tomas; Kurasova, Olga; Filatovas, Ernestas; Igumenov, Aleksandr; Ivanikovas, Sergėjus (Lietuvos matematikos rinkinys, 2016)
In this paper, effective utilization of processors in computer cluster is investigated. Generally, a computer cluster is treated as a specially designed system only for solving specific computationally intensive and time consuming problems. Commonly, computers in offices and universities are idle for a considerable proportion of the time. Therefore, in this research, we focus on exploitation of such computational resources. The experimental investigationshows that when executing multiple processes in each CPU core allows to solve computationally intensive problems more precisely compared to the case, where the number of processes is equal to the number of CPU cores, meanwhile the same amount of energy is consumed in both cases.
Keywords: parallel computing; computer cluster; processor utilization; power consumption and savings